Contrasting particle fluxes and composition in a submarine canyon affected by natural sediment transport events and bottom trawling - Paradis, Sarah; Arjona-Camas, Marta; Goñi, Miguel; Palanques, Albert; Masqué, Pere; Puig, Pere (Frontiers in Marine Science, 2022)
Submarine canyons are important conduits of sediment and organic matter to deep-sea environments, mainly during high-energy natural events such as storms, river floods, or dense shelf water cascading, but also due to human activities such as bottom trawling. The contributions of natural and trawling-induced sediment and organic matter inputs into Palamós Canyon (NW Mediterranean) were assessed from three instrumented moorings deployed in the axis and northern flank of the canyon covering the trawling closure (February) and the trawling season (March-December) of 2017. During the trawling closure, large sediment fluxes with high contents of labile marine organic matter content were registered in the canyon axis, associated to storm resuspension on the shelf that coincided with dense shelf water cascading and high surface water productivity. Although no major natural sediment transport events occurred during the following spring and summer months, near-daily trawling-induced sediment gravity flows were recorded in the northern flank mooring, placed directly below a fishing ground, which sometimes reached the canyon axis. Compositionally, the organic matter transferred by trawling resuspension was impoverished in the most labile biomarkers (fatty acids, amino acids, and dicarboxylic acids) and had a high degree of degradation, which was similar to surficial sediment from the adjacent fishing ground. Trawling resuspended particles masked the transfer of organic matter enriched in labile biomarkers that naturally occur during the quiescent summer months. Overall, bottom trawling enhances the magnitude of particle fluxes while modifying its organic carbon composition, increasing the re-exposure and transfer of degraded organic carbon and potentially affecting benthic communities that rely on the arrival of fresh organic matter.